Compliance and satisfaction with lockdown during the COVID-19 pandemic in Argentina and exploration of its psychological impact (Actualizaciones en Sida e Infectología, 2021)
In response to the spread of the COVID-19 pandemic, Argentina implemented social, preventive, and mandatory lockdown (SPML). This study analyzed factors associated with compliance and satisfaction with the SPML 30 days after its implementation in Argentina and self-reported emotional responses to this measure. An online survey, designed ad hoc, was answered by 2,965 participants from the 24 districts of the country between April 18 and 21, 2020. From them, 68.4% (n = 2021) were female and 31.6% (n = 935) were male. The mean age was 43.49 years (SD = 14.97). Chi-square tests and logistic regression analysis were performed to explore associations between different variables and levels of compliance and satisfaction. Emotional responses were qualitatively analyzed. Belonging to a group at risk for COVID-19, having experienced a reduction in household income, and greater satisfaction with the SPML were associated with higher odds of total compliance. Lower satisfaction was associated with being male, belonging to a group at risk for COVID-19, prioritizing economy as much as (or more than) health, and having experienced a reduction in household income. The most frequently reported emotional responses were related to anxiety and negative or depressed affect, although coping strategies and positive emotions were also mentioned. These results contribute to generating recommendations to improve the effectiveness of the implementation of these measures for the control of the COVID-19 pandemic.
Keywords: COVID-19; pandemics; quarantine; compliance; satisfaction; psychological distress